Incorporation of natural wound healer (honey) into hydrogel - Ab. Hadi, Hazrina; Abdul Jalil, Mohd Azri; Kasmuri, Abdul Razak (2017)
Hydrogels possess an exceptional three-dimensional cross linked networks of hydrophilic polymers that able to imbibe a large proportion of water while maintaining the structure. For hydrogel mixture, 10% polyvinyl alcohol (PVA) and 1% polyethylene glycol (PEG) were used. This was mixed with 1% protein-free agar solution (w/v), and 2% dextran (w/v). When the temperature reached 45°C, 6% honey (v/v) of honey was added. For a control hydrogel, similar mixture was prepared with the exclusion of honey. They were frozen at −20°C for 18 h and then thawed at 25°C for 6 h to complete a cycle (F-T cycle). The pieces of hydrogel samples (2×2 cm) were dried at 60°C in the oven for 12 hours (Wa). Then, they were soaked in pH 7.4 phosphate buffer solution (PBS) and put inside the oven at 37°C (Ws) for 24 hours. The swelling ratio (SR) was calculated accordingly. Meanwhile, the gel fraction was determined by drying hydrogel samples (2×2 cm) for 6 h at 50°C in the oven (Wo). They were soaked in 10 mL distilled water into Petri dishes for 24 hour up to a constant weight and taken out from Petri dishes in order to remove the soluble parts. The gels were dried again at 50°C under vacuum (We). For the swelling ratio test, hydrogels that were lowly cross-linked showed a higher water uptake since a highly cross-linked structure unable to preserve much water in its structure. Formulation containing honey showed lower swelling ability, compared to control. It can be postulated by the present of agar that can hinder its swelling ability. Since there is no active ingredient (honey) in control formulation, the gel fraction of the hydrogel is highest indicating that the PVA in this formulation was almost completely cross-linked. Hence, honey concentration could be used to control the strength and increase the flexibility the hydrogel. In conclusion, hydrogel with 10% honey concentration demonstrated low swelling index but better flexibility than the control formulation.